2019
DOI: 10.1111/ans.15012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of website information provided by paediatric surgery centres in Australia and New Zealand

Abstract: Background: Hospital websites are an important source of information for patients, parents and healthcare providers. There are currently no standardized recommendations for the information provided on paediatric surgery websites. We aimed to assess the information available on each hospital website, in Australia and New Zealand, which provides paediatric surgical care. Methods: Google search was performed of the 16 paediatric surgical centres in Australia and New Zealand to determine whether they had a hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This percentage was much higher than a previous review of pediatric surgical centers by Meiyappan et al, which found that only 68.8% of teams had a website available. 15 This may reflect increasing demand and Internet usage over time. [6][7][8][9] This study found that the majority of centers (79.7%) were updated in the year of 2022.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This percentage was much higher than a previous review of pediatric surgical centers by Meiyappan et al, which found that only 68.8% of teams had a website available. 15 This may reflect increasing demand and Internet usage over time. [6][7][8][9] This study found that the majority of centers (79.7%) were updated in the year of 2022.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Previously, studies have investigated the health information of surgery center and hospital websites. 15,16 The aim of this study is to perform a comprehensive assessment of online resources related to diagnosis, evaluation, treatment, perioperative instructions, and presence of updated information by ACPA-approved teams. In addition, this study investigated the impact of regional differences and hospital rankings with the presence of patient education information.…”
Section: Introductionmentioning
confidence: 99%
“…According to a report by the China Internet Network Information Center, as of March 2020, the penetration rate of internet users in China was 64.5%, which represents an increase of 4.9% when compared to this penetration rate in 2018 [2]. Most adults use the internet to access health care information to support health care decisions [3,4], and a hospital's home page can serve as the first point of contact to provide health care information services for consumers. Thus, in the internet era, the hospital website has become an important window connecting various departments of a hospital with patients and society, as well as a fairly new marketing tool to current and potential customers [5].…”
Section: Introductionmentioning
confidence: 99%
“…The subject of hospital website evaluation has been heavily researched in different studies, such as an analysis of private hospital websites promoting medical tourism in India, Malaysia, and Thailand [8]; an evaluation of the quality of private hospital websites in Turkey; an evaluation of top academic hospitals for finding endocrine surgeons [7]; an evaluation of website information provided by pediatric surgery centers in Australia and New Zealand [4]; and a ranking of children's hospital websites in the United States [9]. However, previous studies have not fully examined the evaluation of websites of general or large hospitals.…”
Section: Introductionmentioning
confidence: 99%